Evaluasi Terhadap Necessary Boredom Thesis Menurut Bernard Williams Terkait Kematian dan Kehidupan Setelah Kematian - Wahyudi, Arief (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2023)
The sitcom “The Good Place” tells the story of an imaginary afterlife where everyone in heaven is in an unhappy state (ironically called the “good” place). All the fun things they can do in eternity to the point that everyone gets bored and eventually the meaning in their lives disappears. Seeing death as the source of meaning in life on earth, the solution in this story is to bring death back to heaven. The view that eternity will lead to boredom is based on Bernard Williams’ Necessary Boredom Thesis. Williams argues that when humans do not experience death (immortality), there is a meaning in life that will be lost. The author sees that this view raises questions in two important respects: First, how do believers view the perspective of death as the source of life’s meaning? Second, what is the believer’s perspective on immortality and boredom in the new heaven and new earth—in other words, is immortality something bad and not to be coveted? This paper first examines the philosophical assumptions behind the Necessary Boredom Thesis and shows that compared to the Christian worldview, this thesis does not see human beings holistically, thus making life only partially construed. Secondly, this paper evaluates this thesis with the biblical concept of identity and the new heaven and earth, so that eternity can be interpreted without boredom because we have a relationship with God.